Determination of Anti‐Parkinson Drug Pramipexole Using a Label‐free Biosensor and Evaluation of its Interaction with ds‐DNA. Issue 5 (7th December 2021) - Mahmoudi‐Moghaddam, Hadi; Garkani‐Nejad, Zahra
Abstract: In this study, we fabricated an effective and sensitive DNA biosensor based on flower‐like Pt/NiCo2 O4 modified carbon paste electrode (FL‐Pt/NiCo2 O4 /CPE) for detection of pramipexole (PPX). Spectrophotometry, differential pulse voltammetry (DPV) and docking methods were employed to evaluate the interaction of DNA‐PPX. Moreover, the DPV technique was chosen to monitor the electrochemical response of guanine on the DNA biosensor. The relationship between the concentration of PPX and the oxidation signal of guanine was linear in the range of 0.4 to 310.0 μM and a limit of detection (LOD) of 0.09 μM was calculated. Abstract :